Persepsi Mahasiswa Baru Terhadap Pemanfaatan Konferensi Video dalam Keterampilan Berbicara Bahasa Mandarin - Wardi, Prayoga Mahaputra (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2023)
The Covid-19 pandemic has forced teachers and students to make adjustments. To train production and interaction in Chinese speaking skills, one of the adjustments made is to use video conference-based learning media. The pandemic conditions have resulted in 2 batches of UNJ PSPBM students who from the start have never participated in face-to-face learning. The purpose of this study was to determine the perception of UNJ PSPBM students who had never participated in face-to-face learning on the use of video conference-based learning media in PJJ basic level speaking skills. Perceptions were researched using Davis's theory of the Technology Acceptance Model (TAM), which was seen from the ease of use and usefulness. This research is a descriptive qualitative research with survey method. Respondents in this study were 45 students of PSPBM UNJ class of 2020 and 2021 participants of basic listening and speaking courses for the 2020/2021 and 2021/2022 academic years. The results showed that according to students who had never participated in face-to-face learning, the video conferencing-based learning media used by PJJ Chinese speaking skills was easy to use and useful. This can be taken into consideration to continue the use of video conferencing-based learning media as an online PJJ learning media for basic level Mandarin speaking skills.